Dielectric ceramic material, manufactured ceramic antenna substrate and manufacturing process

CN122897677APending Publication Date: 2026-10-13XINHUA HENGRUI ELECTRONIC CERAMIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611120694.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]本发明的目的在于提供一种介质陶瓷材料、制得的陶瓷天线基片及制备工艺,以解决现有介质陶瓷材料中谐振频率温度系数τf与品质因数Q×f难以兼顾、添加剂分散不均导致晶粒异常长大、排胶残碳使介电损耗增加、以及烧结降温过程晶界应力无法释放导致Q×f降低的问题

Benefits of technology

①本发明通过TiO2-MgO-BaCO3-CaCO3四元体系与La2O3、ZnO的协同掺杂,配合烧结活化组分的助烧作用,在保证谐振频率温度系数稳定的同时获得了优异的品质因数,并实现了充分致密化烧结,获得了优异介电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897677A_ABST
    Figure CN122897677A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of ceramic materials, and discloses a dielectric ceramic material, a prepared ceramic antenna substrate and a preparation process. The dielectric ceramic material comprises a main dielectric ceramic system, a doping modification component, a dielectric regulation component and a sintering activation component. The main system is composed of TiO2, MgO, BaCO3 and CaCO3. The doping modification component comprises ZnO, and the dielectric regulation component comprises La2O3. The preparation adopts step-by-step ball milling. The dielectric regulation component is firstly ball milled with pre-sintered powder to a fine particle size, and then the doping modification component and the sintering activation component are added for second-stage ball milling. The green body is subjected to sectional variable-rate degassing in an oxygen-rich atmosphere and then is subjected to sectional sintering. The prepared ceramic antenna substrate comprises MgTiO3-based main crystal phase, second phase and grain boundary glass phase distributed between the crystal grains, has high densification degree and high quality factor, and has stable resonance frequency temperature coefficient. The problems of sintering non-densification, abnormal grain growth and electric performance fluctuation of the existing materials are solved, and the application is suitable for high-performance radio frequency communication equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic materials technology, specifically relating to a dielectric ceramic material, a ceramic antenna substrate, and a preparation process. Background Technology

[0002] Dielectric ceramic materials are a class of functional ceramic materials with specific dielectric constants, dielectric losses, and temperature coefficients of resonant frequencies. They are widely used in radio frequency communication fields such as satellite navigation, mobile communication, the Internet of Things, and autonomous driving. Ceramic antenna substrates made from dielectric ceramic materials have advantages such as stable dielectric properties, high mechanical strength, good dimensional stability, resistance to high and low temperatures, and ease of miniaturization and integration. They are important basic materials for dielectric antennas, dielectric resonators, and other microwave radio frequency devices. With the rapid development of multi-system satellite navigation and fifth-generation and sixth-generation mobile communication technologies, higher requirements are placed on the dielectric properties, dimensional stability, and batch consistency of dielectric ceramic materials and ceramic antenna substrates.

[0003] BaO-MgO-TiO2 and MgTiO3-CaTiO3 systems are commonly used microwave dielectric ceramic material systems. However, there is a trade-off between the temperature coefficient τf of the resonant frequency and the quality factor Q×f when adjusting these materials—this can be addressed by adding Ca. 2+ Or Ba 2+ Temperature compensation often leads to a significant decrease in Q×f, and the selection and ratio of dopants in existing modification schemes lack systematicity, making it difficult to achieve synergistic optimization of dielectric properties and sintering characteristics.

[0004] Currently, solid-state reaction is the main method for preparing this type of material, but the following problems still exist: the amount of additives added is relatively small, and traditional single-stage ball milling is difficult to achieve uniform dispersion, which easily leads to local compositional segregation and abnormal grain growth, resulting in large batch-to-batch dispersion of dielectric properties; the binder removal process is crude, and the residual carbon produced by the decomposition of the binder will ignite Ti at high temperatures. 4+ Restored to Ti 3+ This generates oxygen vacancies and electronic defects, causing a sharp increase in dielectric loss. The lack of control over the sintering cooling process leads to abnormal grain growth during the cooling stage. At the same time, the thermal stress at the grain boundaries cannot be effectively released, resulting in uncontrolled crystallization of the amorphous grain boundary phase, which significantly reduces the Q×f value.

[0005] Furthermore, in the mass production of ceramic antenna substrates, processes such as pressing, sintering shrinkage, and subsequent processing are interconnected. Insufficient process control precision can easily lead to dielectric constant dispersion, increased dimensional deviations, and resonant frequency drift, thereby affecting antenna impedance matching performance, radiation efficiency, and product consistency. As radio frequency devices develop towards multi-band, miniaturization, and high integration, existing dielectric ceramic materials and their preparation processes still have shortcomings in terms of dielectric properties, dimensional stability, process stability, and batch consistency, making it difficult to meet the application requirements of high-performance ceramic antenna substrates.

[0006] Therefore, it is necessary to provide a dielectric ceramic material, a ceramic antenna substrate made from it, and its fabrication process to improve the overall performance of the dielectric ceramic material and the manufacturing stability of the ceramic antenna substrate, so as to meet the application requirements of modern radio frequency communication equipment for high-performance dielectric ceramic materials. Summary of the Invention

[0007] The purpose of this invention is to provide a dielectric ceramic material, a ceramic antenna substrate, and a fabrication process to solve the problems in existing dielectric ceramic materials, such as the difficulty in balancing the temperature coefficient of resonant frequency τf and the quality factor Q×f, uneven dispersion of additives leading to abnormal grain growth, residual carbon after binder removal increasing dielectric loss, and the inability to release grain boundary stress during sintering and cooling, resulting in a decrease in Q×f.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A dielectric ceramic material, comprising the following components by mass percentage: Main dielectric ceramic system: 90%–92%; Doping modification components: 1%–3%; Dielectric modulator components: 1%–3%; Sintering activation component: 0.5%–2%; The main dielectric ceramic system is composed of TiO2, MgO, BaCO3 and CaCO3; the doping modification component includes ZnO; the dielectric regulation component includes La2O3; the sintering activation component includes at least one of V2O5, Bi2O3, CuO and B2O3-ZnO-SiO2 glass powder.

[0009] As a further technical solution of the present invention, in the main dielectric ceramic system, the molar ratio of (MgO+BaCO3+CaCO3) to TiO2 is (0.95~1.02):1; and the mass ratio of BaCO3 to CaCO3 is (1~2):(2~5).

[0010] As a further technical solution of the present invention, the doping modification component further includes MnO2 and / or Co2O3; the mass ratio of ZnO to MnO2 and / or Co2O3 is (2-5):1.

[0011] As a further technical solution of the present invention, the dielectric control component further includes Nd2O3 and / or Sm2O3; the mass ratio of La2O3 to Nd2O3 and / or Sm2O3 is (1~3):1.

[0012] As a further technical solution of the present invention, the sintering activation component is a combination of V2O5 and CuO, or a combination of Bi2O3 and B2O3-ZnO-SiO2 glass powder; in the B2O3-ZnO-SiO2 glass powder, the molar ratio of B2O3, ZnO and SiO2 is (2-4):(3-5):(1-3).

[0013] As a further technical solution of the present invention, the relative density of the dielectric ceramic material is not less than 98% of the theoretical density, the quality factor Q×f≥50000GHz, the temperature coefficient of the resonant frequency τf is -5~+5ppm / ℃, and the dielectric constant is stable in the test frequency range of 1~10GHz.

[0014] The present invention also provides a ceramic antenna substrate made using the above-mentioned dielectric ceramic material, comprising a substrate body, wherein the substrate body comprises a MgTiO3-based main crystalline phase, and a second phase and a grain boundary glass phase distributed between the grains of the main crystalline phase; the D of the main crystalline phase grains... 50 The range is 1.0–4.0 μm.

[0015] As a further technical solution of the present invention, at least one surface of the substrate body is provided with a metal electrode layer, and the material of the metal electrode layer is silver, copper or silver-copper alloy.

[0016] The present invention also provides a process for fabricating the above-mentioned ceramic antenna substrate, comprising the following steps: S1. Weigh TiO2, MgO, BaCO3 and CaCO3 as the main medium ceramic raw materials according to the ratio, mix them and then ball mill them for the first time. After drying and sieving, pre-fire them at 850℃~1150℃ for 2~5h to carry out decarbonation and solid-phase reaction to obtain the main crystalline phase pre-fired powder. S2. Add La2O3 dielectric modulator to the pre-calcined powder and perform the first stage of ball milling to reduce the median particle size D. 50 Reduced to ≤0.8μm; then added ZnO doped modification components and sintering activation components for a second stage of ball milling, resulting in a final powder median particle size D. 50 The particle size is controlled between 0.6 and 1.2 μm. After adding a binder, the particles are spray-granulated to obtain granulated powder. S3. The granulated powder is pressed into a green body, and the green body is placed in an oxygen-rich atmosphere for segmented variable-rate debinding treatment: first, the temperature is raised to 280℃~350℃ at a heating rate of 0.2~0.5℃ / min and held for 2~4h, then the temperature is raised to 500℃~550℃ at a heating rate of 1.0~1.5℃ / min and held for 1~3h, controlling the residual carbon mass percentage of the green body after debinding to be ≤0.02%; S4. The green blank after debinding is sintered in sections, cooled, and then processed to obtain the ceramic antenna substrate.

[0017] As a further technical solution of the present invention, the segmented sintering in step S4 includes: The temperature is increased to 1300℃~1380℃ at a heating rate of 3~6℃ / min, and held for 2~4h to densify the ceramic matrix. The temperature was lowered to 1100℃~1150℃ at a cooling rate of 5~8℃ / min to suppress abnormal growth of the main crystalline phase grains; The temperature is lowered to 1050℃ to 1090℃ at a cooling rate of 0.5 to 1℃ / min and held for 1 to 3 hours to promote the reconstruction of the liquid phase micro-regions at the grain boundaries and release thermal stress; then the furnace is cooled to room temperature.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: ① This invention achieves excellent quality factor while ensuring stable temperature coefficient of resonant frequency by synergistic doping of TiO2-MgO-BaCO3-CaCO3 quaternary system with La2O3 and ZnO, combined with the sintering-aiding effect of sintering activation components, and obtains excellent dielectric properties by fully densifying sintering.

[0019] ② A step-by-step ball milling process is adopted. First, the dielectric control component and the pre-calcined powder are ball milled to a fine particle size. Then, the doping modification component and the sintering activation component are added for a second stage of ball milling. This allows each component to be uniformly coated on the surface of the powder particles step by step, which significantly improves the consistency of the microstructure and reduces the batch dispersion of dielectric properties.

[0020] ③ In an oxygen-rich atmosphere, segmented variable-rate debinding is employed. Debinding is carried out at an extremely slow heating rate within the main decomposition zone of the binder, followed by complete oxidation upon heating. This keeps the residual carbon content at an extremely low level, effectively suppressing Ti oxidation. 4+ The restoration ensures the realization of high-quality factors.

[0021] ④ A three-stage sintering process of "densification → rapid cooling → slow cooling annealing" is adopted. Rapid cooling inhibits abnormal growth of main crystalline phase grains, and slow cooling annealing promotes the reconstruction of micro-regions of liquid phase at grain boundaries and releases thermal stress. Finally, a microstructure with uniform and controllable grain size is obtained, which ensures the consistency of product performance and batch stability. Attached Figure Description

[0022] Figure 1 This is a schematic flowchart illustrating the fabrication process of a ceramic antenna substrate according to the present invention. Figure 2 This is a schematic diagram of the overall structure of the ceramic antenna substrate; Figure 3 This is a schematic diagram of the cross-sectional structure of a ceramic antenna substrate; In the figure: 1. Substrate body; 2. Feed hole. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] Example 1 This embodiment provides a dielectric ceramic material, the composition and content of which are as follows: Main dielectric ceramic system: 91%; Doping modification component: 2.5%; Dielectric modulator component: 2.5%; Sintering activation component: 1.5%; In the main dielectric ceramic system, the mass ratio of TiO2, MgO, BaCO3 and CaCO3 is 1:1 (MgO+BaCO3+CaCO3):TiO2, and the mass ratio of BaCO3 to CaCO3 is 1.5:3.5; the doping modification component is ZnO; the dielectric regulation component is La2O3; and the sintering activation component is a combination of V2O5 and CuO, with a mass ratio of V2O5 to CuO of 1:1.

[0025] like Figure 1 As shown, the preparation method of the dielectric ceramic material in this embodiment is as follows: S1. Main Material Synthesis and Pre-firing: Weigh TiO2, MgO, BaCO3, and CaCO3 as the main ceramic media according to the above proportions. Mix the main components and then perform the first ball milling. The ball milling conditions are as follows: use deionized water as the medium, place the raw materials, ball beads, and water in a planetary ball mill at a mass ratio of 1:3:1.5, the ball milling speed is 250 r / min, and the ball milling time is 8 h. Place the ball-milled slurry in an oven and dry it at 100℃ to constant weight, then pass it through a 60-mesh sieve. Place the sieved mixed powder in an alumina crucible and heat it to 1150℃ in a high-temperature furnace at a heating rate of 5℃ / min. Pre-firing for 3 h carries out decarbonation and solid-phase reaction. After cooling in the furnace, the pre-fired powder of the main crystalline phase is obtained.

[0026] S2. Stepwise composite ball milling: First-stage ball milling: La2O3 dielectric modifier is added to the pre-calcined powder. The milling conditions are: deionized water as the medium, material:ball:water mass ratio of 1:3:1.5, rotation speed of 300 r / min, and milling for 6 hours to reduce the median particle size D50 to 0.72 μm. Second-stage ball milling: ZnO doping modifier and sintering activation components (V2O5 and CuO) are added. The milling conditions are: rotation speed of 200 r / min, and milling for 4 hours to control the final median particle size D50 of the powder to 0.85 μm. Then, 8% (by weight) of polyvinyl alcohol (PVA) binder aqueous solution is added, and spray granulation is performed to obtain granulated powder. The moisture content of the granulated powder is controlled at 0.5%.

[0027] S3. Molding and Fine Debinding: The granulated powder is pressed into a green body. The pressing process combines dry pressing and isostatic pressing: first, dry pressing pre-forming is performed at 20 MPa, followed by isostatic pressing at 150 MPa for 3 minutes. The green body is then placed in an oxygen-enriched atmosphere (oxygen concentration ≥30%) for segmented variable-rate debinding: first, the temperature is increased to 300℃ at a rate of 0.3℃ / min and held for 3 hours for debinding; then, the temperature is increased to 520℃ at a rate of 1.2℃ / min and held for 2 hours to completely eliminate internal residual carbon. Thermogravimetric analysis shows that the residual carbon percentage of the green body after debinding is 0.015%.

[0028] S4. Segmented Densification Sintering: The green body after binder removal is sintered in segments. The temperature is increased to 1350℃ at a heating rate of 5℃ / min and held for 3 hours to densify the ceramic matrix; then the temperature is decreased to 1120℃ at a cooling rate of 6℃ / min to suppress abnormal growth of the main crystalline phase grains; then the temperature is decreased to 1070℃ at a cooling rate of 0.8℃ / min and held for 2 hours to promote the reconstruction of the liquid phase micro-regions at the grain boundaries and release thermal stress; finally, the furnace is cooled to room temperature to obtain the ceramic antenna substrate.

[0029] like Figure 2 and Figure 3 As shown, the ceramic antenna substrate fabricated in this embodiment includes a square substrate body 1 with rounded corners. A feed aperture 2 is formed on the substrate body 1 and is eccentrically arranged. The feed aperture 2 is recessed inward from one side surface of the substrate body 1 and does not penetrate the substrate body 1; a chamfer is provided at the opening of the feed aperture 2. The feed aperture 2 is used to accommodate the conductive feed structure, forming the antenna's RF feed point. The eccentric arrangement of the feed aperture 2 allows for adjustment of the antenna feed point position, optimizing the antenna's resonance characteristics and impedance matching effect. The chamfer at the opening of the feed aperture 2 forms an inclined surface, facilitating the assembly and alignment of the feed structure, while also eliminating sharp edges at the opening, preventing chipping or damage to the ceramic substrate.

[0030] The performance of the ceramic antenna substrate prepared in this embodiment was tested: The volume density was determined using Archimedes' displacement method, and the relative density was calculated to be 98.5% of the theoretical density.

[0031] The dielectric properties were tested using a vector network analyzer at a frequency of 10 GHz using the resonant cavity method: the dielectric constant εr was 20.5; the quality factor Q×f was 52300 GHz.

[0032] The temperature coefficient τf of the resonant frequency was measured using a variable temperature test method within a temperature range of -40℃ to +85℃, and the calculated value of τf was -2.3ppm / ℃.

[0033] The microstructure of the substrate was observed using field emission scanning electron microscopy (FE-SEM) combined with energy dispersive spectroscopy (EDS). The results showed that the substrate mainly consisted of a MgTiO3-based main crystalline phase (EDS analysis showed enrichment of Mg, Ti, and O elements). Between the main crystalline phase grains were distributed a second phase (EDS analysis showed enrichment of Ca and La elements) and a grain boundary glassy phase (EDS analysis showed enrichment of Si, Zn, and B elements). The D-values ​​of the MgTiO3-based main crystalline phase grains were... 50 The grain size was 2.3 μm (obtained by counting at least 200 grains using the cut-off method), with uniform distribution and no abnormal grain growth observed.

[0034] Example 2 This embodiment provides a dielectric ceramic material, the composition and content of which are as follows: Main dielectric ceramic system: 90%; Doping modification component: 3%; Dielectric modulation component: 3%; Sintering activation component: 2%; In the main dielectric ceramic system, the mass ratio of TiO2, MgO, BaCO3, and CaCO3 is 0.98:1 (MgO+BaCO3+CaCO3):TiO2, and the mass ratio of BaCO3 to CaCO3 is 1.2:2.8. The doping modification component is a combination of ZnO and MnO2, with a mass ratio of ZnO to MnO2 of 3:1. The dielectric regulation component is a combination of La2O3 and Nd2O3, with a mass ratio of La2O3 to Nd2O3 of 2:1. The sintering activation component is a combination of Bi2O3 and B2O3-ZnO-SiO2 glass powder, with a molar ratio of B2O3, ZnO, and SiO2 in the B2O3-ZnO-SiO2 glass powder of 3:4:2.

[0035] The preparation method in this embodiment is basically the same as that in Example 1, except that: The pre-firing temperature in S1 is 1150℃, and the pre-firing time is 4 hours; S2, after the first stage of ball milling, D 50The final D after the second stage of ball milling is 0.68μm. 50 It is 0.78 μm; The debinding parameters in S3 are: heat up to 320℃ at 0.4℃ / min and hold for 3.5h, then heat up to 530℃ at 1.3℃ / min and hold for 2.5h. The sintering parameters for S4 are as follows: heat up to 1360℃ at 4℃ / min and hold for 3.5h, cool down to 1130℃ at 7℃ / min, and then cool down to 1080℃ at 0.7℃ / min and hold for 2.5h.

[0036] The performance of the ceramic antenna substrate prepared in this embodiment was tested: The relative density is 98.7% of the theoretical density; the dielectric constant εr is 20.1; the quality factor Q×f is 53800 GHz; the temperature coefficient of resonant frequency τf is -1.8 ppm / ℃; SEM-EDS observation shows that the MgTiO3-based main crystalline phase grains are D 50 The thickness is 2.0 μm, and the second phase and grain boundary glass phase are uniformly distributed.

[0037] Example 3 This embodiment provides a dielectric ceramic material, the composition and content of which are as follows: Main dielectric ceramic system: 92%; Doping modification component: 1.5%; Dielectric modulator component: 1.5%; Sintering activation component: 0.5%; In the main dielectric ceramic system, the mass ratio of TiO2, MgO, BaCO3, and CaCO3 is 1.02:1 (MgO+BaCO3+CaCO3):TiO2, and the mass ratio of BaCO3 to CaCO3 is 1.8:4.2. The doping modification component is a combination of ZnO and Co2O3, with a mass ratio of ZnO to Co2O3 of 4:1. The dielectric regulation component is a combination of La2O3 and Sm2O3, with a mass ratio of La2O3 to Sm2O3 of 2.5:1. The sintering activation component is a combination of V2O5 and CuO, with a mass ratio of V2O5 to CuO of 1.2:1.

[0038] The preparation method in this embodiment is basically the same as that in Example 1, except that: The pre-firing temperature in S1 is 1150℃, and the pre-firing time is 2.5h; S2, after the first stage of ball milling, D 50 The final D after the second stage of ball milling is 0.75μm. 50 It is 0.92 μm; The debinding parameters in S3 are: heat up to 280℃ at 0.25℃ / min and hold for 4 hours, then heat up to 500℃ at 1.0℃ / min and hold for 3 hours; The sintering parameters for S4 are as follows: heat up to 1320℃ at 3.5℃ / min and hold for 4 hours, then cool down to 1110℃ at 5.5℃ / min, and then cool down to 1060℃ at 0.9℃ / min and hold for 3 hours.

[0039] The performance of the ceramic antenna substrate prepared in this embodiment was tested: The relative density is 98.3% of the theoretical density; the dielectric constant εr is 19.8; the quality factor Q×f is 51500 GHz; the temperature coefficient of resonant frequency τf is -3.1 ppm / ℃; SEM-EDS observation shows that the MgTiO3-based main crystalline phase grains are D 50 The thickness is 2.8 μm, and the second phase and grain boundary glass phase are uniformly distributed.

[0040] Comparative Example 1 This comparative example provides a dielectric ceramic material whose composition is basically the same as that of Example 1, except that: the main dielectric ceramic system does not contain BaCO3, but is composed only of TiO2, MgO and CaCO3 (i.e., MgTiO3-CaTiO3 binary system), the molar ratio of (MgO+CaCO3):TiO2 is maintained at 1.0:1, and the CaCO3 content is the same as the total amount of BaCO3+CaCO3 in Example 1.

[0041] The preparation method is the same as in Example 1.

[0042] The performance of the ceramic antenna substrate prepared in this comparative example was tested: The relative density is 97.2% of the theoretical density; the dielectric constant εr is 19.5; the quality factor Q×f is only 38600 GHz; the temperature coefficient of resonant frequency τf is -18.6 ppm / ℃; SEM-EDS observation shows that the main crystalline phase of MgTiO3 is uneven in size and has obvious abnormally large grains.

[0043] Comparative Example 2 This comparative example provides a dielectric ceramic material with the same composition as in Example 1. The difference lies in the preparation method, where the second ball milling is performed using a traditional single-stage ball milling method (non-step ball milling, all additives are added and milled simultaneously to D). 50 (0.85μm).

[0044] The performance of the ceramic antenna substrate prepared in this comparative example was tested: The relative density is 97.8% of the theoretical density; the dielectric constant εr is 20.2; the quality factor Q×f is 42500 GHz; the temperature coefficient of the resonant frequency τf is -5.2 ppm / ℃; SEM-EDS observation shows that there are local compositional segregation regions in the MgTiO3-based main crystal phase, and the second phase aggregation is obvious.

[0045] Comparative Example 3 This comparative example provides a dielectric ceramic material with the same composition as Example 1. The difference is that the debinding stage in the preparation method adopts conventional single-stage debinding (directly heating to 500℃ at 1.5℃ / min and holding for 3h without controlling the atmosphere).

[0046] The performance of the ceramic antenna substrate prepared in this comparative example was tested: The relative density is 98.1% of the theoretical density; the dielectric constant εr is 20.3; the quality factor Q×f is only 35900 GHz; and the temperature coefficient of resonant frequency τf is -4.8 ppm / ℃. Thermogravimetric analysis showed that the residual carbon content after debinding was 0.085%, and EDS analysis showed carbon enrichment at the grain boundaries.

[0047] Comparative Example 4 This comparative example provides a dielectric ceramic material with the same composition as Example 1. The difference is that the sintering stage in the preparation method adopts conventional single-stage sintering (heating to 1350℃ at 5℃ / min, holding for 5h and then cooling with the furnace, without segmented temperature control).

[0048] The performance of the ceramic antenna substrate prepared in this comparative example was tested: The relative density is 98.0% of the theoretical density; the dielectric constant εr is 20.6; the quality factor Q×f is 40800 GHz; the temperature coefficient of the resonant frequency τf is -3.5 ppm / ℃; SEM-EDS observation shows that there are obvious abnormally large grains in the MgTiO3-based main crystalline phase (some grains are larger than 15 μm), and microcracks are visible at the grain boundaries.

[0049] The compositional features, process features, and main performance test results of each embodiment and comparative example are summarized in Table 1.

[0050] Table 1: Comparison of composition, process, and performance of each embodiment and comparative example

[0051] As shown in Table 1, comparing Example 1 with Comparative Example 1, it is evident that without the addition of BaCO3 (i.e., the traditional MgTiO3-CaTiO3 binary system), Q×f significantly decreased (from 52300 GHz to 38600 GHz), and τf deteriorated to -18.6 ppm / ℃. This indicates that Ba... 2+The introduction of [a specific ingredient] plays a crucial role in achieving a high quality factor and stable temperature drift. This invention utilizes the addition of BaCO3 to [a specific ingredient]... 2+ It enters the main lattice to form a solid solution, which effectively improves the dielectric properties.

[0052] Comparing Example 1 with Comparative Example 2, it can be seen that when using conventional single-stage ball milling, Q×f drops to 42500 GHz, and τf also deteriorates slightly. This illustrates that the step-by-step ball milling process—first ball milling the La2O3 dielectric modifier component and pre-sintered powder to a fine particle size, then adding the ZnO doped modification component and sintering activation component for a second stage of ball milling—ensures that each component is uniformly coated on the surface of the powder particles step by step, which is of great significance for improving the consistency of microstructure and dielectric properties.

[0053] Comparing Example 1 with Comparative Example 3, it can be seen that when using conventional single-stage debinding, the residual carbon content significantly increases (from 0.015% to 0.085%), and Q×f drops sharply to 35900GHz. This indicates that residual carbon has a significant impact on Ti... 4+ The reduction of Ti is the main cause of dielectric loss degradation. This invention employs segmented variable-rate debinding in an oxygen-rich atmosphere, debinding at an extremely slow heating rate in the main decomposition zone of the binder, followed by complete oxidation upon heating, thus controlling the residual carbon content to an extremely low level and effectively inhibiting Ti degradation. 4+ The restoration ensures the realization of high Q×f.

[0054] Comparing Example 1 with Comparative Example 4, it can be seen that although the density is basically the same when using conventional single-stage sintering, Q×f drops to 40800 GHz, and SEM observation reveals obvious abnormal grain growth and microcracks. This indicates that the three-stage sintering process of "densification → rapid cooling → slow cooling annealing" in this invention, rapid cooling suppresses abnormal growth of the main crystalline phase grains, and slow cooling annealing promotes the reconstruction of liquid phase micro-regions at grain boundaries and releases thermal stress, which plays an irreplaceable role in achieving high Q×f and uniform microstructure.

[0055] The dielectric ceramic material, the resulting ceramic antenna substrate, and the fabrication process provided by this invention have widely available and low-cost raw materials. The fabrication process is highly compatible with existing solid-state reaction equipment and requires no special equipment investment. Through the synergistic control of the BaO-MgO-TiO2-CaO quaternary system with La2O3 and ZnO, stepwise ball milling, oxygen-enriched segmented glue removal, and segmented sintering processes, stable mass production can be achieved. The resulting ceramic antenna substrate exhibits excellent performance (Q×f≥50000GHz, τf is -5~+5ppm / ℃), making it suitable for manufacturing ceramic antenna substrates and dielectric resonators in fields such as satellite navigation, 5G / 6G mobile communication base station antennas, IoT and vehicle networking RF front-end modules.

[0056] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A dielectric ceramic material, characterized in that, By mass percentage, it includes the following components: Main dielectric ceramic system: 90%–92%; Doping modification components: 1%–3%; Dielectric modulator components: 1%–3%; Sintering activation component: 0.5%–2%; The main dielectric ceramic system is composed of TiO2, MgO, BaCO3 and CaCO3; the doping modification component includes ZnO; the dielectric regulation component includes La2O3; the sintering activation component includes at least one of V2O5, Bi2O3, CuO and B2O3-ZnO-SiO2 glass powder.

2. The dielectric ceramic material according to claim 1, characterized in that, In the main dielectric ceramic system, the molar ratio of (MgO+BaCO3+CaCO3) to TiO2 is (0.95~1.02):1; and the mass ratio of BaCO3 to CaCO3 is (1~2):(2~5).

3. The dielectric ceramic material according to claim 1, characterized in that, The doping modification components also include MnO2 and / or Co2O3; the mass ratio of ZnO to MnO2 and / or Co2O3 is (2-5):

1.

4. The dielectric ceramic material according to claim 1, characterized in that, The dielectric control component further includes Nd2O3 and / or Sm2O3; the mass ratio of La2O3 to Nd2O3 and / or Sm2O3 is (1-3):

1.

5. The dielectric ceramic material according to claim 1, characterized in that, The sintering activation component is a combination of V2O5 and CuO, or a combination of Bi2O3 and B2O3-ZnO-SiO2 glass powder; in the B2O3-ZnO-SiO2 glass powder, the molar ratio of B2O3, ZnO and SiO2 is (2-4):(3-5):(1-3).

6. The dielectric ceramic material according to claim 1, characterized in that, The relative density of the dielectric ceramic material is not less than 98% of the theoretical density, the quality factor Q×f ≥ 50000 GHz, the temperature coefficient of the resonant frequency τf is -5 to +5 ppm / ℃, and the dielectric constant is stable in the test frequency range of 1 to 10 GHz.

7. A ceramic antenna substrate, made of the dielectric ceramic material according to any one of claims 1-6, characterized in that, The substrate comprises a MgTiO3-based main crystalline phase, and a second phase and a grain boundary glass phase distributed between the grains of the main crystalline phase; the D of the main crystalline phase grains... 50 The range is 1.0–4.0 μm.

8. The ceramic antenna substrate according to claim 7, characterized in that, At least one surface of the substrate body is provided with a metal electrode layer, and the material of the metal electrode layer is silver, copper or silver-copper alloy.

9. A process for fabricating a ceramic antenna substrate, characterized in that, Includes the following steps: S1. Weigh TiO2, MgO, BaCO3 and CaCO3 as the main medium ceramic raw materials according to the ratio, mix them and then ball mill them for the first time. After drying and sieving, pre-fire them at 850℃~1150℃ for 2~5h to carry out decarbonation and solid-phase reaction to obtain the main crystalline phase pre-fired powder. S2. Add La2O3 dielectric modulator to the pre-calcined powder and perform the first stage of ball milling to reduce the median particle size D. 50 Reduced to ≤0.8μm; then added ZnO doped modification components and sintering activation components for a second stage of ball milling, resulting in a final powder median particle size D. 50 The particle size is controlled between 0.6 and 1.2 μm. After adding a binder, the particles are spray-granulated to obtain granulated powder. S3. The granulated powder is pressed into a green body, and the green body is placed in an oxygen-rich atmosphere for segmented variable-rate debinding treatment: first, the temperature is raised to 280℃~350℃ at a heating rate of 0.2~0.5℃ / min and held for 2~4h, then the temperature is raised to 500℃~550℃ at a heating rate of 1.0~1.5℃ / min and held for 1~3h, controlling the residual carbon mass percentage of the green body after debinding to be ≤0.02%; S4. The green blank after debinding is sintered in sections, cooled, and then processed to obtain the ceramic antenna substrate.

10. The preparation process according to claim 9, characterized in that, The segmented sintering described in step S4 includes: The temperature is increased to 1300℃~1380℃ at a heating rate of 3~6℃ / min, and held for 2~4h to densify the ceramic matrix. The temperature was lowered to 1100℃~1150℃ at a cooling rate of 5~8℃ / min to suppress abnormal growth of the main crystalline phase grains; The temperature is lowered to 1050℃ to 1090℃ at a cooling rate of 0.5 to 1℃ / min and held for 1 to 3 hours to promote the reconstruction of the liquid phase micro-regions at the grain boundaries and release thermal stress; then the furnace is cooled to room temperature.